2020
DOI: 10.3389/fimmu.2020.572747
|View full text |Cite
|
Sign up to set email alerts
|

MAVS Deficiency Is Associated With a Reduced T Cell Response Upon Secondary RSV Infection in Mice

Abstract: Infections with respiratory syncytial virus (RSV) occurs repeatedly throughout life because sustained, protective memory responses fail to develop. Why this occurs is not known. During RSV infection the recognition of the virus via the cytosolic RIG-I like receptors and signaling via the adaptor protein MAVS is crucial for mounting an innate immune response. However, if this signaling pathway is important for T cell responses during primary infection and during re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
(92 reference statements)
1
10
0
Order By: Relevance
“…One day after re-infection, neutrophil numbers peaked in the airways and lung tissue while alveolar macrophage (AM) numbers remained overall unchanged during the re-infection period (S2A-S2C Fig) . These responses are very similar to what is observed during primary infection [32,33] but to a much lower magnitude. Naïve CD4 + and CD8 + T cell numbers in the lung remained constant, yet as expected, total CD8 + and CD4 + T cell numbers increased during re-infection (S2D-S2G Fig) . The numbers of total CD4 + and CD8 + T cells at day 4 post re-infection were comparable to numbers recorded at the peak of the primary infection (day 7-8) in this model [32,39,40]. The increase was driven mainly by an expansion in the number (g) Stacked analysis of the subpopulations of CD8 + T EF cells bases on expression of CD103 and/or CD69.…”
Section: Lung T Rm Cells Expand Post Rsv Re-infectionsupporting
confidence: 64%
See 4 more Smart Citations
“…One day after re-infection, neutrophil numbers peaked in the airways and lung tissue while alveolar macrophage (AM) numbers remained overall unchanged during the re-infection period (S2A-S2C Fig) . These responses are very similar to what is observed during primary infection [32,33] but to a much lower magnitude. Naïve CD4 + and CD8 + T cell numbers in the lung remained constant, yet as expected, total CD8 + and CD4 + T cell numbers increased during re-infection (S2D-S2G Fig) . The numbers of total CD4 + and CD8 + T cells at day 4 post re-infection were comparable to numbers recorded at the peak of the primary infection (day 7-8) in this model [32,39,40]. The increase was driven mainly by an expansion in the number (g) Stacked analysis of the subpopulations of CD8 + T EF cells bases on expression of CD103 and/or CD69.…”
Section: Lung T Rm Cells Expand Post Rsv Re-infectionsupporting
confidence: 64%
“…During RSV re-infection, despite major differences in T RM cell numbers and function in wt mice compared with Mavs -/-, we found no differences in viral load at day 2 post re-infection although, in these experiments, wt mice showed slightly faster viral clearance than Mavs -/mice at day 4 post re-infection. However, low viral load may contribute to some experimental variability as we had previously found no difference in viral load day 4 post re-infection [39]. Arguing for a role of T RM cell in RSV control, other groups have shown that, in the absence of antibodies, adoptive transfer of airway CD8 + T cells is enough to control disease development [18].…”
Section: Plos Pathogensmentioning
confidence: 77%
See 3 more Smart Citations